EKSISTENSI KOPERASI WANITA DALAM MENINGKATKAN PENDAPATAN MASYARAKAT - Syahriyah Semaun (AL-MAIYYAH : Media Transformasi Gender dalam Paradigma Sosial Keagamaan, 2018)
The existence of women's cooperatives in Indonesia is significant even though there are not many large female cooperatives, but women's cooperatives are capable of assisting the government in overcoming national problems such as reducing unemployment, improving health, improving education and addressing gender issues. Cooperatives are a place for women to improve their family economy, self-actualization for women. Women are no longer just housewives but cooperatives have proven their superiority in empowering women as pioneers in helping micro-businesses in their region. Therefore women's cooperatives need to be grown and encouraged.